Perancangan Tampilan Website Klinik Pajak Ramah UMKM Dengan Pendekatan Evaluating Tax Sites: An Evaluation Framework (TSEF) - Prayuda, Muhammad Bagus; Arniati, Arniati (Pusat P2M Politeknik Negeri Batam, 2023)
The development of technology and information in the globalization era caused significant changes in various fields. This research aims to analyze and design a tax information system for micro, small and medium enterprises (MSMEs). Data was collected through interviews and group discussions with several MSMEs using the TSEF Framework (TSEF), which focuses on discussions related to Display, Multimedia and Format to create a user-friendly website. The aspects examined are colour display, fonts, multimedia and formatting. The research results showed that the colour chosen by respondents was green, the font used was sans-serif, and the multimedia used was an explanatory video related to tax information.